(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Alluvial and glaciofluvial sand and gravel deposits are the significant natural resources of the Augšdaugava spillway valley. Considering that these sediments differ in granulometric composition and degree of sorting, which in turn determine their utilisation, it is substantially to distinguish sediments of different origin. Hence the main objective of this study was to assess grain size distribution and micromorphology of quartz grains as indicators for distinguishing alluvial and glaciofluvial sands. The grain size distribution has been identified by the laser diffraction method, but the micromorphology of quartz grains has been analysed by scanning electron microscopy. The obtained data indicate that results of the granulometric composition analysis can be used for the discrimination of alluvial and glaciofluvial sediments, in contrast, micromorphology cannot be a reliable diagnostic indicator for identifying the sand of different origin.